The growing child : laying the foundations of active learning and physical health - Stevens, Clair (London ; New York : Routledge, 2013)
"How do children's early physical experiences influence their future health and well-being? The Growing Child thoughtfully discusses the key principles of children's physical development alongside descriptions of everyday practice. It looks in detail at all aspects of physical development including exercise, diet, sleep and how these link to the development of the whole child. The book considers key learning dispositions such as perseverance, determination, confidence, responsibility, courage and curiosity and shows how physical play helps to develop children's organisational skills, team work, risk management, communication and raise their self-esteem. Drawing on the author's own experience of running a Forest School nursery, the book aims to help practitioners to: - create rich and stimulating play environments that enable children to learn, make connections and explore using their whole bodies; - reflect on their own teaching methods to encourage children's engagement, motivation and creativity through effective observation and planning; - engage with parents and carers to help support children's learning at home whilst maintaining the values of the family; - celebrate the uniqueness of each child and provide learning experiences that are appropriate for individuals with particular learning needs, be they physical, emotional or cognitive to ensure that every child has an equal opportunity to succeed. Emphasising the importance of understanding the theory that underpins children's physical development, this accessible text shows practitioners how they can use this knowledge to provide learning opportunities that nourish children's health, learning and well-being"--
"A David Fulton book"--cover.
Includes bibliographical references and indexes.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Play; Early childhood education; Physical education and training; Children -- Health and hygiene; Active learning; Electronic books